Konsep Value For Money untuk Pengukuran Kinerja pada Kantor Imigrasi Pangkalpinang - Yunita Maharani; Rafika Sari (Politeknik Negeri Bengkalis, 2021)
This research intends to determine the performance of immigration office pangkalpinang in 201-2020 based on: 1) economy ratio, 2) efficiency ratio, and (3)effectiveness ratio. This research is a descriptive by analyzing progress report of immigration in pangkalpinang 2018-2020. Data collection method is documentation and Data analysis tool is value for money concept. The results of the research concludes that the performance Office immigration on has been: 1) economically with economy ratio averagely under 100%; 2) efficiently conducted with efficiency averagely under 100%; 3) effectively conducted with effectivenessration of 100% in average. Keywords: economy, efficiency, and effectiveness